A new construction of two-, three- and few-weight codes via our GU codes and their applications - Eddie, Arrieta A; Janwa, Heeralal (Applicable algebra in engineering, communication and computing, 2022)
Linear codes with few weights have applications in cryptography, association schemes, designs, strongly regular graphs, finite group theory, finite geometries, and secret sharing schemes, among other disciplines. Two-weight linear codes are particularly interesting because they are closely related to objects in different areas of mathematics such as strongly regular graphs, 3-rank permutation groups, ovals, and arcs. There exist techniques to construct linear codes with few weights, for example, the systematic exposition by Calderbank and Kantor (Bull Lond Math Soc 18(2):97–122, 1986 ). Ding et al., (World Sci, pp 119–124, 2008 ) and (IEEE Trans Inf Theory 61(11):5835–5842, 2015 ) constructed few-weight codes using the trace function and Tonchev et al. (Algorithms, 12(8), 2019 ) generalized Ding’s construction. In this paper, we present an elementary way to get two- and three-weight codes from simplex codes and antipodal linear codes. An interesting application is the construction of uniformly packed linear codes from two-weight codes and quaternary quasi-perfect linear codes from three-weight codes.